Draft Annual Plan 1972-1973 Government of the Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1972)
During the earlier regime, as there was no restriction on import the industrial development of the Territory was totally reflected. However a few industries flourished under the protection of India Economic Blockade. One peculiar feature after liberation in the structure of Goa economy is the increase in the prices of agricultural products leading to rise in the agriculture incomes and resulting in a comparatively larger investment in the agricultural field.
Planning Department
Planning Department